ISLAMIC FINANCE AS A STRATEGIC POINT FOR THE DEVELOPMENT OF RUSSIA - I. A. Zaripov (Финансы: теория и практика, 2017)
The paper describes the author’s view on the current political and financial challenges facing the Russian Federation, particularly aggravated by recent economic crises, falling export prices and sanctions of some Western countries. Proofs of the need to revise the concept and strategy of the country’s development as well as the basic principles used in financial interrelations are provided. The author comes to the conclusion about the urgency and need to develop alternative finance, primarily based on Islamic financial principles (conformant to the Islamic law). Islamic financial institutions, in particular, should be partners for the fast growing sector of the halal products and services production.